2016
DOI: 10.3389/fpls.2016.00843
|View full text |Cite
|
Sign up to set email alerts
|

Complete Chloroplast Genome of Nicotiana otophora and its Comparison with Related Species

Abstract: Nicotiana otophora is a wild parental species of Nicotiana tabacum, an interspecific hybrid of Nicotiana tomentosiformis and Nicotiana sylvestris. However, N. otophora is least understood as an alternative paternal donor. Here, we compared the fully assembled chloroplast (cp) genome of N. otophora and with those of closely related species. The analysis showed a cp genome size of 156,073 bp and exhibited a typical quadripartite structure, which contains a pair of inverted repeats separated by small and large si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
95
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(126 citation statements)
references
References 66 publications
31
95
0
Order By: Relevance
“…When less genomic resources are available for revealing divergence hotspot regions, the oligonucleotide repeats might be utilized as a substitute for identifying polymorphic regions (Ahmed et al, 2012; Ahmad, 2014). The current study results of oligonucleotide repeats are similar to the previously reported results of Nicotiana species and other angiosperm plastome studies (Asaf et al, 2016; Yang et al, 2019). Thus, the presence of both the high divergence regions in IGS and oligonucleotide repeats suggest that these regions are suitable for the development of markers to demonstrate phylogenetics relationships.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When less genomic resources are available for revealing divergence hotspot regions, the oligonucleotide repeats might be utilized as a substitute for identifying polymorphic regions (Ahmed et al, 2012; Ahmad, 2014). The current study results of oligonucleotide repeats are similar to the previously reported results of Nicotiana species and other angiosperm plastome studies (Asaf et al, 2016; Yang et al, 2019). Thus, the presence of both the high divergence regions in IGS and oligonucleotide repeats suggest that these regions are suitable for the development of markers to demonstrate phylogenetics relationships.…”
Section: Discussionsupporting
confidence: 92%
“…Here, we detected that the mononucleotide repeats (A/T), and trinucleotide SSRs (ATT/TAA) were present in large amounts in all the species of Nicotiana , which may be a result of the A/T rich proportion of chloroplast genome. A similar result was also reported in Nicotiana otophora (Asaf et al, 2016). In all the species of Nicotiana , the LSC region contained a greater amount of SSRs in comparison to SSC and IR, which has also been demonstrated in other studies of angiosperm plastomes (Shahzadi et al, 2019; Mehmood et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Although cp genomes are highly conserved in terms of genomic structure and size, the IR/SC junction position change caused by expansion and contraction of the IR/SC boundary regions was usually considered as a primary mechanism in creating the length variation of the higher plant cp genomes (Kim and Lee, 2005; Asaf et al, 2016; Dong et al, 2016; Yang et al, 2016; Zhang et al, 2016). In this study, however, the IR/SC junction position change was not observed among the six cp genomes.…”
Section: Resultsmentioning
confidence: 99%
“…In Nicotiana otophora , all mono-nucleotides (100%) are composed of A/T (Asaf et al, 2016). In the five Epimedium cp genomes, mono-nucleotide SSRs were found to be the richest, up to 72.76%, and the mono-nucleotide A/T repeat units occupied 80.17% in the homopolymer SSRs.…”
Section: Resultsmentioning
confidence: 99%
“…sacra and Azadirachta indica . Missing and ambiguous gene annotations were confirmed by comparative sequence analysis after a multiple sequence alignment and gene order comparison [43]. These regions were aligned using MAFFT (version 7.222) [44] with the default parameters.…”
Section: Methodsmentioning
confidence: 99%